Clinical-morphological aspects of the instability of hip joint endoprosthesis - Filipenko, Volodymyr; Dedukh, Ninel; Shkodovskaya, Natalya; Tankut, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article presents data of clinical observations and a histological study of the periprosthesis tissues, got from patients after the revision hip joint replacement owing to aseptic instability. The accumulation of metal microparticless and polyethylene fragments, accompanied by an increase in macrophage density, is shown. The most pronounced destructive changes were present, if polyethylene was worn out.